Manuskrip Al-Qur’ān Oversize Ms Codex 2047 Koleksi Universitas Pennsylvania: Analisis Filologi - Abdul Qawwiy Nasrun (UIN Sunan Kalijaga Yogyakarta, 2026)
Nusantara Qur'anic manuscripts serve as key artefacts that record the history of Islamic transmission and acculturation, yet many of them remain philologically unidentified. This study aims to analyse the codicological characteristics and the application of rasm 'Uthmānī in the Manuscript al-Qur’ān Oversize MS Codex 2047, which is presumed to originate from Indonesia. Using a descriptive qualitative approach and the library research method, data were analysed through direct study of the manuscript's digital images from the University of Pennsylvania, as well as primary and secondary literature related to codicology and Qur'anic orthography in the Nusantara tradition. The findings reveal that the manuscript possesses distinctive physical features, such as floral illuminations in red, gold, and black, as well as a mature systemsistem of recitational markers and navigational signs. Textually, the manuscript demonstrates inconsistent application of rasm 'Uthmānī, with numerous deviations towards rasm imlā’ī, indicating a copying strategy prioritising readability. It is concluded that Manuskrip al-Qur’ān Oversize MS Codex 2047 represents an adaptive tradition of Qur'anic copying in the Nusantara, creating a hybrid form between orthographic authenticity and pedagogical accessibility. Abstrak Manuskrip al-Qur’ān Nusantara berperan sebagai artefak kunci yang merekam sejarah transmisi dan akulturasi Islam, namun banyak di antaranya belum teridentifikasi secara filologis. Penelitian ini bertujuan untuk menganalisis karakteristik kodikologi dan penerapan rasm 'Uṡmānī pada Manuskrip al-Qur’ān Oversize MS Codex 2047 yang diduga berasal dari Indonesia. Dengan menggunakan pendekatan kualitatif deskriptif dan metode kajian pustaka (library research), data dianalisis melalui studi langsung terhadap citra digital manuskrip dari Universitas Pennsylvania serta literatur primer dan sekunder terkait kodikologi dan rasm Mushaf Nusantara. Hasil penelitian menunjukkan bahwa naskah ini memiliki ciri fisik khas seperti iluminasi floral berwarna merah, emas, dan hitam, serta sistem penanda tajwid dan navigasi yang matang. Secara tekstual, naskah menunjukkan penerapan rasm 'Uṡmānī yang tidak konsisten dengan banyak penyimpangan ke arah rasm imlā’ī, mengindikasikan strategi penyalinan yang mengutamakan kemudahan bacaan. Disimpulkan bahwa Manuskrip al-Qur’ān Oversize MS Codex 2047 merepresentasikan tradisi penyalinan mushaf Nusantara yang adaptif, menciptakan bentuk hibrida antara otentisitas ortografis dan aksesibilitas pedagogis.